Bone morphogenic protein expression and bone formation are induced by bioactive glass S53P4 scaffolds in vivo. Issue 3 (8th September 2018) - Björkenheim, Robert; Strömberg, Gustav; Ainola, Mari; Uppstu, Peter; Aalto‐Setälä, Laura; Hupa, Leena; Pajarinen, Jukka; Lindfors, Nina C.
Abstract: The two‐stage induced‐membrane (IM) technique is increasingly used for treatment of large bone defects. In stage one, the bone defect is filled with polymethylmethacrylate (PMMA), which induces a membrane around the implant. In stage two, PMMA is replaced with bone graft. Bioactive glasses (BAGs) are bone substitutes with bone‐stimulating and angiogenic properties. We have previously shown that a certain type of BAG can also induce a foreign‐body membrane similar to PMMA. The aim of this study was to evaluate the bone‐forming capacity of sintered BAG‐S53P4 and poly(lactide‐ co ‐glycolide) (PLGA)‐coated BAG‐S53P4 scaffolds for potential use as bone substitutes in a single‐stage IM technique. Sintered porous rods of BAG‐S53P4, BAG‐S53P4‐PLGA, or PMMA were implanted in rabbit femurs for 2, 4, or 8 weeks. The expression of bone morphogenic protein (BMP)‐2, ‐4, and ‐7 in the IMs of implanted materials were analyzed with real‐time quantitative polymerase chain reaction. Micro‐computed tomography imaging was used to evaluate bone growth and further verified with scanning electron microscopy. BAG‐S53P4 and BAG‐S53P4‐PGLA scaffold IMs show similar or superior expression of BMP‐2, ‐4, and ‐7 compared with PMMA IM. Bone ingrowth into BAG scaffolds increased over time. Active bone formation occurred inside the BAG scaffolds and the respective BMP expressions were similar or superior for the BAG IMs compared with PMMA, thus making BAGs a promising device for single‐stage treatment of bone defects. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res B Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 847–857, 2019.